PENGARUH KOMPETENSI APARATUR PEMERINTAH TERHADAP KUALITAS PELAYANAN PUBLIK PADA KANTOR KECAMATAN SANGATTA SELATAN KABUPATEN KUTAI TIMUR - Salasiah dan Eli Ampung (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
This research is based on the competence of government apparatus in southern Sangatta kecmatan in hopes to improve the quality of public services.The purpose of this study is to determine whether the competence of the government apparatus affect the quality of public services at the district office very districts kutai east. The type of research or explanation used is descriptive kuanlitatif used to analyze the relationship between research variables. Types of data used are kusioner, observation, interview, and documentation.The result of partial test on the independent variable that is the Competence variable of government apparatus toward the variable of public service quality shows the result that have significant influence that is by showing from t count> t table, 3.304> 1675. With R obtained for 0.776, which means that 77.6% Competence the government apparatus has a positive impact on service quality and 22.4% is influenced by other factors not discussed in this study.